Use of fluorescent angiography with indocyanine green for prediction of hypocalcemia development after thyroidectomy - V. K. Lyadov; D. R. Pashaeva; M. V. Nekludova (Опухоли головы и шеи)
Introduction. The future of thyroid gland fast-track surgery depends largely on early hypocalcemia prediction. We describe our experience of using intraoperative indocyanine green fluorescent angiography (IGFA) of parathyroid glands to access their function in the early postoperative period.The study objective is to evaluate the possibility of prediction of early postoperative hypocalcemia after thyroidectomy using intraoperative indocyanine green fluorescent angiography.Materials and methods. Thirty five (35) patients with benign and malignant thyroid tumors eligible for thyroidectomy were included in the study. Intraoperative IGFA was performed using the SPY SP2000 (Novadaq Technologies Inc., Canada) device and visual assessment of vascularization of the parathyroid glands. The glands without fluorescence were considered ischemic. Ionized calcium test was performed 4, 8, and 18–24 hours after the surgery. Significance of the difference in its levels in patients with normal and ischemic parathyroid glands was evaluated.Results. In 26 patients, vascularization was considered sufficient, in 9 patients the glands were ischemic per the fluorescent examination.Statistically significant difference of ionized calcium levels were observed between groups with ischemic and normal glands at 18 hours after the surgery (mean 1.060 ± 0.53 in ischemic vs. 1.110 ± 0.56 in normal group, p <0.05).Conclusion. Intraoperative IGFA of the parathyroid glands can successfully predict early postoperative hypocalcemia. Further studies for accessing correlation with permanent hypocalcemia are required.